Spirolide uptake and detoxification by Crassostrea gigas exposed to the toxic dinoflagellate Alexandrium ostenfeldii - Medhioub, Walid; Lassus, Patrick; Truquet, Philippe; Bardouil, Michèle; Amzil, Zouher; Sechet, Véronique; Sibat, Manoella; Soudant, Philippe (Aquaculture, 2012)
International audience Oysters (Crassostrea gigas) were exposed 4 days to cultures of the toxic dinoflagellate Alexandrium ostenfeldii (strain CCMP1773) that produces spirolides belonging to fast acting toxins (FAT) and let depurate for 7 days. During depuration, oysters were either fed the non-toxic algae Isochrysis galbana Tahitian clone (T. Iso) or starved. The objectives of this experiment were to evaluate (i) spirolide uptake and depuration by oysters (ii) spirolide effects on oysters and (iii) oyster recovery according to food supply during depuration. A. ostenfeldii cells were filtered and ingested by oysters while faeces contained numerous intact cells of the toxic diet. This suggested that ingested cells were not totally digested by oysters. Contents of spirolides (SPX) in digestive gland and remaining tissues during contamination and detoxification periods were measured by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Four different SPX analogues (13,19-didesMeC, 13-desMeC, 13-desMeD and trace of SPX-D) were detected. The 13,19-didesMeC-SPX dominated in both digestive gland and remaining tissues. After four days exposure, digestive gland (DG) contained 83% of the total initial spirolide concentration, whereas remaining tissues contained only 17%. During detoxification, spirolide content in DG was lower in fed than in unfed oysters but similar in remaining tissues. Exposure to A. ostenfeldii resulted in an inflammatory response consisting of hemocyte infiltration and diapedesis into the intestinal tract of the oysters. Percentage of active digestive tubules in oysters fed A. ostenfeldii was significantly lower than in control (prior exposition) oysters (36% and 61%, respectively). At the end of the detoxification period, there was a significant difference in the percentage of active digestive tubules (P < 0.001) between fed and unfed oysters. When oysters were fed T-Iso following the A. ostenfeldii exposure, 80% of digestive tubules were active, thus revealing a rapid ...